Analisis kinerja Badan Usaha Milik Desa dalam pengelolaan anggaran untuk meningkatkan pengolahan potensi desa di Desa Akedotilou - Madjodjo, Farid; Dahlan, Fadli (Indonesia Accounting Journal, 2020)
This study uses qualitative approach with purpose to determine: (1) the performance of BUMDes in budget management; and (2) the performance of the "Karivela" BUMDes in managing village potential in Akidotilou Village of Oba Tengah District in Tidore Kepulauan City of North Maluku Province. Data collection techniques through observation, interviews, documentation, and literature study. Data analysis procedures include data collection, data reduction, data presentation, and drawing conclusions. The results show that budget management by BUMDes "Karivela" which should be accountable for budget management to the Village Government of Akedotilou Oba Tengah Subdistrict Tidore Islands City has not been carried out by BUMDes "Karivela" officials. So that every BUMDes "Karivela" budget is known to lack transparency, both in management and accountability. Meanwhile, in the management of village potential in the Village managed by BUMDes "Karivela" there is still no improvement in the existing business units. this is because the management of the BUMDes "Karivela" does not have the ability to manage the village potential in Akedotilou village and the lack of human resources who manage the village potential.